2003
DOI: 10.1186/1297-9686-35-1-77
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genes influencing economic traits in three French dairy cattle breeds

Abstract: -A project of QTL detection was carried out in the French Holstein, Normande, and Montbéliarde dairy cattle breeds. This granddaughter design included 1 548 artificial insemination bulls distributed in 14 sire families and evaluated after a progeny-test for 24 traits (production, milk composition, persistency, type, fertility, mastitis resistance, and milking ease). These bulls were also genotyped for 169 genetic markers, mostly microsatellites. The QTL were analysed by within-sire linear regression of daughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
4
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(89 citation statements)
references
References 25 publications
9
75
4
1
Order By: Relevance
“…However, fast-milking cows may be at increased risk for mastitis [44]. The significantly associated SNPs in the peak on BTA6 for milking speed found in this study overlapped with a previously identified QTL in three French dairy cattle breeds [45]. Interestingly, the association signal is located close to IL8 (Additional file 5: Figure S4B), a known member of interleukin family.…”
Section: Discussionsupporting
confidence: 63%
“…However, fast-milking cows may be at increased risk for mastitis [44]. The significantly associated SNPs in the peak on BTA6 for milking speed found in this study overlapped with a previously identified QTL in three French dairy cattle breeds [45]. Interestingly, the association signal is located close to IL8 (Additional file 5: Figure S4B), a known member of interleukin family.…”
Section: Discussionsupporting
confidence: 63%
“…The QTL on OAR9 and OAR17 aligned to QTL for the same milk persistence characteristics reported on the orthologous bovine chromosomes (BTA14 and BTA17, respectively) [12,29]. The QTL for milk persistency on BTA14 had its peak within the region of the DGAT1 gene.…”
Section: Resultssupporting
confidence: 53%
“…And, the SNP on BTA25 associated with animal size is near TMEM130 and is within a QTL region that has been reported to affecting calf size in Danish Holstein cattle [37]. Besides, most of significant SNPs that we detected in this study are located within QTL regions that have been reported previously to affect production, longevity, and reproduction traits in dairy cattle [21,35,36,38,39]. …”
Section: Discussionsupporting
confidence: 58%